2019
DOI: 10.3389/fmicb.2019.01322
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Seroconversion Duration of HIV-1 Antibodies in Individuals With Recent Infection in China

Abstract: The identification of recent HIV-1 infection is clinically important for the effective treatment and prevention of transmission. However, the window period for seroconversion with respect to various HIV-1 antibodies is not well characterized. In addition, the routine HIV testing algorithms are not particularly appropriate for the identification of recent HIV-1 infection. In this study, we enrolled individuals who showed seroconversion from negative Western blot (WB) or indeterminate WB results and analyzed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…The incubation period for MPXV can range from 5 up to 21 days, 1,3 whereas HIV seroconversion times range between 15-60 days. 8 It is likely that the MPXV lesions facilitated HIV transmission, by disrupting the anal mucosal integrity. Interestingly, clinical manifestation of MPXV (fever, rash, lymphadenopathy, etc.,) are the same as those observed in acute HIV infection, making differential diagnosis even more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The incubation period for MPXV can range from 5 up to 21 days, 1,3 whereas HIV seroconversion times range between 15-60 days. 8 It is likely that the MPXV lesions facilitated HIV transmission, by disrupting the anal mucosal integrity. Interestingly, clinical manifestation of MPXV (fever, rash, lymphadenopathy, etc.,) are the same as those observed in acute HIV infection, making differential diagnosis even more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…They are able to detect HIV specific antibodies in most subjects, but acute HIV infection and late-stage HIV infection maybe negative or indeterminate for HIV antibody tests [ 3 , 21 – 23 ]. Previous studies have proven that the sequential emergence of HIV-1 antibodies associates with the progress of HIV-1 infection [ 11 , 12 , 24 – 26 ], therefore the laboratory diagnosis of HIV infection is helpful for understanding the local epidemic and may partly reflect the effectiveness of HIV/AIDS intervention. Our data indicated that, although the number of suspected samples gradually grown in Wuhan, the positive rate of HIV-1 antibodies has declined significantly during 2012–2018.…”
Section: Discussionmentioning
confidence: 99%
“…In the same time, the recent HIV-1 infection and suspected acute HIV infection seem to be increased, which may be caused by the extensive usage of the sensitive 4 th generation ELISA and/or chemiluminescence immunoassay (CLIA) kits in China, and may also be associated with the efforts of China in intervening HIV infection among high risk population in recent years [ 27 , 28 ]. Previous studies have reported that the number, intensity and order of emergence of WB bands were affected by the stage of HIV infection [ 10 , 11 ], and pol antibodies may be predictors of seroconversion [ 4 ], especially p31 [ 10 , 20 , 29 – 31 ] and p66 [ 12 ]. In this study, we identified that the absence rates of p31, p66, and p51 were 17.03%, 9.40%, and 15.15% respectively and all of them increased significantly from 2012 to 2018.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV-1 nucleic acid test (NAT), in addition, is recommended for HIV-1 screening and diagnosis, especially for acute HIV-1 Infected and advanced AIDS patients. However, due to the cost and technical barriers, their use as general screening and diagnostic tools is limited [1]. The level of viral replication determined by the HIV-1 p24 capsid protein is quantified using the ELISA antigen capture assay, which is time consuming and produces false positive and/or negative results.…”
Section: Introduction:mentioning
confidence: 99%